A review of studies on the impact of hydrogen-blended natural gas on the performance of terminal gas equipment - Jianguo FENG; Hengjin LUO; Chaokui QIN; Dongqing PENG; Zhiguang CHEN; Jian CAI (You-qi chuyun, 2025)
ObjectiveHydrogen-blended natural gas presents a viable solution for facilitating the large-scale application of hydrogen. However, the introduction of hydrogen can significantly alter the physical property parameters of the gas, leading to various operational challenges in terminal equipment, such as combustion oscillations, decreased thermal loads, and increased risks of flashback. To promote the widespread adoption of hydrogen-blended natural gas, it is crucial to identify the impact of various hydrogen blending ratios on the performance of gas equipment. Additionally, evaluating the safety adaptability, combustion characteristics, and emission performance of terminal gas equipment is essential. MethodsThis paper presents a systematic investigation into the impact of hydrogen blending on terminal gas equipment, employing a combination of theoretical analysis, literature review, and case studies. By examining simulations and combustion experiments of hydrogen-blended natural gas conducted both in China and abroad, the study focuses on the changes and effects induced by hydrogen blending, particularly in terms of natural gas physical properties, combustion stability, thermal efficiency, and pollutant emissions. Based on the findings, research into high hydrogen blending ratios is identified as a critical area for future studies. ResultsHydrogen blending in natural gas is associated with several changes and effects, including decreased density, calorific values, and ignition energy; increased combustion temperatures and speeds; shortened quenching distances; elevated lean flammability limits; and altered explosion limit ranges. Currently available domestic gas appliances can directly utilize natural gas with hydrogen blending ratios ranging from 0 to 20％. However, specialized gas appliances need to be developed to enhance thermal efficiency and service life in response to the impact of hydrogen blending. Industrial gas equipment can benefit from improved combustion efficiency and reduced carbon emissions due to hydrogen blending. However, challenges such as aggravated combustion oscillations, lowered critical flashback thresholds, increased NOx emissions, and compromised stability and environmental performance need to be addressed. Strategies to mitigate these challenges include the use of novel high-temperature and corrosion-resistant alloy materials, the implementation of adaptive control techniques, and adjustments to process flows, all aimed at minimizing impacts on product quality. In the field of compressed natural gas (CNG) vehicles, hydrogen blending significantly improves the combustion characteristics of natural gas engines, widening lean flammability limits and reducing combustion cyclic variations and harmful gas emissions, with the exception of NOx. Nevertheless, the increase in NOx emissions can be effectively controlled through technical means. ConclusionAlthough progress has been made in domestic studies on hydrogen-blended natural gas combustion technology for terminal gas equipment, most research remains at the laboratory stage and has yet to be verified through real-world market applications. Therefore, long-term field testing in this area is identified as an urgent priority to accelerate progress toward achieving the “dual carbon” goals.